MEDULLARY THYROID CANCER: GENERAL REVIEW - Ayman A. Amin, Hamdy M. Hussein, Ahmed K. Fekry, Mohamed Mubark (Chelonian Research Foundation, 2024)
The thyroid gland in the neck plays a crucial role in metabolism, growth, and calcium regulation. It has two lobes connected by an isthmus and is highly vascularized, receiving blood from the superior and inferior thyroid arteries. Venous drainage occurs through the superior, middle, and inferior thyroid veins, while lymphatic drainage involves nodes around the trachea and neck. Medullary thyroid cancer (MTC), originating from parafollicular C cells, accounts for 4-10% of thyroid cancers and can be sporadic or hereditary. Diagnosis includes fine-needle aspiration, calcitonin, and CEA levels, with imaging for metastasis. Treatment often involves thyroidectomy and lymph node dissection. Targeted therapies, such as RET-kinase inhibitors, are available for advanced cases. Post-surgery, monitoring serum calcitonin and CEA helps assess recurrence.